2015
DOI: 10.1007/s00441-015-2298-1
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord injury repair by implantation of structured hyaluronic acid scaffold with PLGA microspheres in the rat

Abstract: In order to create an optimal microenvironment for neural regeneration in the lesion area after spinal cord injury (SCI), we fabricated a novel scaffold composed of a hyaluronic acid (HA) hydrogel with a longitudinal multi-tubular conformation. The scaffold was modified by binding with an anti-Nogo receptor antibody (antiNgR) and mixed further with poly(lactic-co-glycolic acid) (PLGA) microspheres containing brain-derived neurotrophic factor and vascular endothelial growth factor (HA+PLGA). In the rat, after i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 41 publications
0
36
0
Order By: Relevance
“…Angiogenesis, which occurs during the early stages of traumatic brain injury, stroke and nerve injury, is associated with nerve recovery as sufficient blood supply is a key factor in the creation of an optimal microenvironment for neural regeneration (24,25). Increased angiogenesis during the acute phase following nerve injury is able to stimulate endogenous recovery mechanisms and promote functional recovery (24).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Angiogenesis, which occurs during the early stages of traumatic brain injury, stroke and nerve injury, is associated with nerve recovery as sufficient blood supply is a key factor in the creation of an optimal microenvironment for neural regeneration (24,25). Increased angiogenesis during the acute phase following nerve injury is able to stimulate endogenous recovery mechanisms and promote functional recovery (24).…”
Section: Discussionmentioning
confidence: 99%
“…Guiding of regenerated axons to grow longitudinally through the lesion area is necessary for repairing nerve injury, as linear growth of axons should maintain the native organization and potentially increase the probability of improving functional recovery of the injured nerve (25). Ma et al (27) recently confirmed that scaffolds with longitudinal channels are able to stimulate and guide linear axonal growth following peripheral nerve injury in rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NT-3 has also been administered in a range of studies in association with scaffolds of various types, composed of collagen Houweling, van Asseldonk, et al, 1998;Li et al, 2016;Yao et al, 2013), fibrin (Guo et al, 2007;Taylor, Jones, et al, 2006;Wilems et al, 2015), matrigel (Bamber et al, 2001), hyaluronic acid/PLGA (Wen et al, 2015), chitosan , or hydrogels (Piantino et al, 2006;Tsai et al, 2006). Improved outcomes using a combination of NT-3 gradients, peripheral conditioning lesions, and stromal cell grafts up to 15 months after SCI have also been reported (Kadoya et al, 2009).…”
Section: Neurotrophin-3mentioning
confidence: 99%
“…PLGA is a biodegradable and biocompatible complex [15, 16] that has been utilized as a tissue engineering complex in a number of studies [17-20]. They tend to provide a better cell growth milieu in the conveyance of exogenous cells into the lesion site, promoting and supporting axonal growth towards the damaged neural cells or tissues [21].…”
Section: Introductionmentioning
confidence: 99%